Improving Short Story Reading Text Listening Skills by using the Cooperative Script Learning Model for Class XI Students of SMK Negeri 1 East Halmahera - Agus Hi Jamal (Jurnal Ilmiah Wahana Pendidikan, 2022)
The skill of listening to short stories for class XI students of SMK Negeri 1 East Halmahera is still low. This is because students are less interested in learning to listen to short stories and do not understand the intrinsic elements of short stories in depth so that students have difficulty determining the intrinsic elements of short stories. The use of learning models and learning media is less interesting and boring to make students bored. In addition, the teacher has not been intensively guiding students in learning to listen to short stories. The formulation of the research problem is: (1) how is the quality of the learning process of short story listening skills through the Cooperative Script learning model in class XI students of SMK Negeri 1 East Halmahera; (2) how to improve the short story listening skills of class XI students of SMK Negeri 1 East Halmahera after listening to listening through the Cooperative Script learning model; and (3) what are the changes in the learning behavior of class XISMK Negeri 1 East Halmahera in learning short story listening skills through the Cooperative Script learning model. The objectives of this classroom action research were: (1) to describe the quality of the process of learning short story listening skills through the Cooperative Script learning model for class XI students of SMK Negeri 1 East Halmahera; (2) describe the improvement of short story listening skills for class XI SMK Negeri 1 East Halmahera after listening to learning through the Cooperative Script learning model; and (3) describe changes in the learning behavior of class XI students of SMK Negeri 1 East Halmahera in learning listening skills through the Cooperative Script learning model. This study uses a class action research design. This classroom action research was carried out in two cycles, namely cycle I and cycle II. Each cycle consists of planning, action, observation, and reflection. The subject of this study was the skill of listening to short stories for class XI at SMK Negeri 1 Halmahera Timur.